2016
DOI: 10.1080/19407882.2016.1199385
|View full text |Cite
|
Sign up to set email alerts
|

Women Faculty Distressed: Descriptions and Consequences of Academic Contrapower Harassment

Abstract: Academic contrapower harassment (ACPH) occurs when someone with seemingly less power in an educational setting (e.g., a student) harasses someone more powerful (e.g., a professor). A representative sample of 289 professors from U.S. institutions of higher education described their worst incident with ACPH. Open-ended responses were coded using a keyword text analysis. Compared to the experiences of men faculty, women faculty reported that students were more likely to challenge their authority, argue or refuse … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
43
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(44 citation statements)
references
References 24 publications
1
43
0
Order By: Relevance
“…While I hope professors' mental health is a sufficient reason to put ACPH on any university's or college's radar, another impact of such behaviour is the compromised functioning of the institution itself. Given documented stress arising from ACPH, including a reported desire to leave their jobs (Lampman, Phelps, Bancroft, & Beneke, 2009;Lampman et al, 2016), faculty's job-related outcomes are negatively affected (DeSouza, 2011). This was certainly true in my case.…”
Section: Is It Resolved? One Story Of Academic Contrapower Harassmentmentioning
confidence: 63%
See 2 more Smart Citations
“…While I hope professors' mental health is a sufficient reason to put ACPH on any university's or college's radar, another impact of such behaviour is the compromised functioning of the institution itself. Given documented stress arising from ACPH, including a reported desire to leave their jobs (Lampman, Phelps, Bancroft, & Beneke, 2009;Lampman et al, 2016), faculty's job-related outcomes are negatively affected (DeSouza, 2011). This was certainly true in my case.…”
Section: Is It Resolved? One Story Of Academic Contrapower Harassmentmentioning
confidence: 63%
“…Student-on-faculty harassment is a form "academic contrapower harassment" (ACPH), which "occurs when someone with seemingly less power in an educational setting [e.g., a student] harasses someone more powerful [e.g., a professor]" (Lampman, Crew, Lowery, & Tompkins, 2016, p. 169). Studies demonstrate that faculty members across genders are harassed by students, through a variety of means, and for a variety of reasons (Blizard, 2016;Lampman, 2012;Lampman et al, 2016;MacLennan, 2002). For example, Blizard's (2016) study of one Canadian university found that student-on-faculty cyberbullying mainly, but not exclusively, stems from students' dissatisfaction with their grades.…”
Section: Is It Resolved? One Story Of Academic Contrapower Harassmentmentioning
confidence: 99%
See 1 more Smart Citation
“…A second issue may be expectations to take on extra, undervalued responsibilities aligned with traditional feminine roles, such as advising and service (Eagan & Garvey, 2015; Hart & Cress, 2008; Roos & Gatta, 2009). A third issue is that students often expect female faculty to be more nurturing and may penalize those who are not (Hart & Cress, 2008; Lampman et al, 2016; Lester, 2011). These factors could all contribute to a stressful work life for female faculty and underscore the need to consider multiple dimensions of stress.…”
Section: Gender and Work Stress In Facultymentioning
confidence: 99%
“…Harrass/Ingore/Insult/Assume to be Incompetent 10 Studies (e.g., DeSouza, 2011; Epps, 2016) 12 Studies (e.g., Knepp, 2012;Lampman, 2012) 10 Studies (e.g., Lampman et al, 2016;May & Tenzek, 2018) 14…”
Section: Student -Faculty/teaching Staff (Contra-hierarchical Microagmentioning
confidence: 99%